ANALISIS PENGARUH DUTA MEREK, PENGEMBALIAN DANA DAN POTONGAN HARGA TERHADAP PEMBELIAN IMPULSIF KONSUMEN DI SITUS BELANJA ONLINE SHOPEE (Studi Kasus Pada Konsumen yang Telah Melakukan Transaksi Minimal Satu Kali di Situs Belanja Online Shopee) - Widia Prastiwi; Kadek Ayu Susiani Dewi (Jurnal Ekonomi Bisnis Indonesia, 2022)
The purpose of this study was to determine the effect of brand ambassadors, cashbacks and discounts on consumer impulse buying on the online Shopee. The research method used is a qualitative method that is quantified. The sampling technique used non-probability sampling with incidental sampling. Data collection techniques using a questionnaire. The number of samples is 97 respondents from an infinite population. Partially, the t-test results show that brand ambassadors and cashbacks have no significant effect on impulse buying. Meanwhile, price discounts have a significant effect on impulse buying. The results of the F test state that brand ambassadors, cashbacks and discounts simultaneously have a significant effect on impulse buying. This study obtained an R value of 0.422. This states that the relationship between the independent variables (brand ambassadors, cashbacks and discounts) to the dependent variable (impulse buying) has a moderate correlation. Value Adjusted R Square is 0.152. This means that brand ambassadors, cashbacks and price discounts contribute 15.2% to the impulsive buying variable. While the remaining 84.8% is influenced by other variables that are not included in this research model.